Synthesis and ion recognition studies of novel benzimidazol-5-yl-L-alanines - Esteves, Cátia I. C. (2015)
N-fluorenylmethoxycarbonyl-4-amino-phneylalanine and appropriate heterocyclic aldehydes were used in the synthesis of novel fluorescent unnatural amino acids, namely benzimidazol-5-yl-L-alanines. These new compounds were characterised by the usual spectroscopic techniques. The photophysical properties of the new amino acids were evaluated by UV-Vis absorption and fluorescence spectroscopy in acetonitrile. Interaction studies with biologically and analytically important ions such as Cu2+, Fe3+, Hg2+ and Pd2+, through spectrophotometric and spectrofluorimetric titrations were carried out to assess their potential as chemosensors.